2014
DOI: 10.1002/jcb.24732
|View full text |Cite
|
Sign up to set email alerts
|

Different Role of cAMP Pathway on the Human Mast Cells HMC‐1560 and HMC‐1560,816 Activation

Abstract: HMC-1 are inflammatory cells that release vasoactive substances such as histamine. These cells have the c-kit receptor permanently activated in the membrane due to mutations in the proto-oncogene c-kit: Val-560 → Gly and Asp-816 → Val. Thus, there are two known cellular lines: HMC-1(560) and HMC-1(560,816) . These mutations are involved in a disease called mastocitosys. In the present paper both lines were used to study the influence of cAMP/PKA/PDEs pathway on the histamine release and Ca(2+) signaling since … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…cAMP and its effector, PKA, are implicated in the resolution of acute inflammation [ 87 ] and are generally regarded as anti-inflammatory [ 88 90 ]. Further, cAMP has been shown to inhibit histamine release from human mast cells [ 91 ] and is reported to be key in several endogenous processes involved in preventing acute inflammation from progressing to deleterious chronic inflammation [ 92 ]. HFE reduced WBC and ESR (Table 3 ), both of which are markers of inflammation status [ 55 – 61 ], compared with the CFA arthritic control.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP and its effector, PKA, are implicated in the resolution of acute inflammation [ 87 ] and are generally regarded as anti-inflammatory [ 88 90 ]. Further, cAMP has been shown to inhibit histamine release from human mast cells [ 91 ] and is reported to be key in several endogenous processes involved in preventing acute inflammation from progressing to deleterious chronic inflammation [ 92 ]. HFE reduced WBC and ESR (Table 3 ), both of which are markers of inflammation status [ 55 – 61 ], compared with the CFA arthritic control.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP and its effector, PKA, are implicated in the resolution of acute in ammation (Lima et al, 2017) and are generally regarded as anti-in ammatory (Campo et al, 2012;Oldenburger et al, 2012;Wang et al, 2020). Interestingly, cAMP has been shown to inhibit histamine release from human mast cells (Barreiro-Costa et al, 2014) and is reported to be key in several endogenous processes involved in preventing acute in ammation from progressing to deleterious chronic in ammation (Moore & Willoughby, 1995). Indeed, HFE reduced WBC and ESR (Table 3), both of which may be used as markers of in ammation status (Carr et al, n.d.;Farhangi et al, 2013;Harrison, 2015;Ingelsson et al, 2005;Kounis et al, 2014;Ong et al, 2015;Watson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%